2015
DOI: 10.1017/s1368980014003309
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of food patterns in young Latino children at high risk of obesity

Abstract: Objective: The present paper examines the influence of age and gender on food patterns of Latino children. Design: Data are from baseline of a 5-year, quasi-experimental obesity prevention study: Niños Sanos, Familia Sana (NSFS; Healthy Children, Healthy Families). In 2012, the researchers interviewed Latino parents, using a thirty-item questionnaire to ask about their children's food consumption and feeding practices. Statistical tests included t tests and ANCOVA. Setting: Rural communities in California's Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 45 publications
2
34
1
2
Order By: Relevance
“…[20] The FFQ was collected within a month after first dietary recall administered. The FFQ F/V consumption was calculated by creating a sum of 7 items (fresh fruit, canned fruit, vegetable soup, other cooked vegetables, salsa, lettuce or cabbage, and other vegetables) to produce a score (range: 7-35).…”
Section: Dietary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] The FFQ was collected within a month after first dietary recall administered. The FFQ F/V consumption was calculated by creating a sum of 7 items (fresh fruit, canned fruit, vegetable soup, other cooked vegetables, salsa, lettuce or cabbage, and other vegetables) to produce a score (range: 7-35).…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…The FFQ instrument used in this study has demonstrated construct validity and internal reliability in this population. [20] In another study, children's F/V consumption, as assessed by this FFQ, was correlated with household inventory of F/V. [21] The RRS skin carotenoid skin carotenoid levels of the children were measured during the first visit using the Pharmanex BioPhotonic Scanner (S2 Everest Edition, Pharmanex, Provo, UT, 2007).…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…随着物质资源不断丰富,可选择的食物种类越来越多,儿童对于食物的挑剔程度也随之增长。近期 研究调查了北京、广州、苏州等九个地区城市儿童,结果显示:有六成的儿童存在挑食行为 (Volger, Sheng, Tong, Zhao, Fan, Zhang et al, 2013)。挑食具体表现为:不愿意尝试新食物,对于食物有强烈的偏好 (Taylor, Wernimont, Northstone, & Emmett, 2015;Wardle, Guthrie, Sanderson, & Rapoport, 2001)。研究表明,挑食可 能导致微量元素和蛋白质缺乏等营养问题,还会造成体重偏低 (Volger et al, 2013;Xue, Zhao, Cai, Yang, Szeto, Ma et al, 2014;Yong, Lee, Ke, Zheng, Ma, Gao et al, 2015)。 父母可以通过自身的行为示范,或者通过控制孩子的饮食环境,来影响下一代的饮食行为和习惯, 从而改善其体重和其他营养状况 (Savage, Fisher, & Birch, 2007;Vollmer & Mobley, 2013)。有研究发现,父 母自身规律的进食蔬果行为,及其提供蔬果的丰富程度,都会促进儿童进食蔬菜水果 (Kaiser, Aguilera, Horowitz, Lamp, Johns, Gomez-Camacho et al, 2015;Wyse, Wolfenden, & Bisquera, 2015);反之,孩子则会 较少进食蔬菜水果,较多进食零食 (Jackson, Smit, Manore, John, & Gunter, 2015;Schrempft, Jaarsveld, Fisher, & Wardle, 2015 Table 3. The mediation effect of parental feeding pressure between parental feeding strategy and child's behavior (N = 424) …”
Section: 前言unclassified
“…Supporting our supposition is evidence of the protective effect that living in an immigrant neighborhood has on the diets of Mexican-origin persons in the U.S. (Dubowitz et al 2008b; Kimbro and Denney 2013; Osypuk et al 2009; Park et al 2008; Reyes-Ortiz et al 2009; Wen and Maloney 2011) and the deleterious effect of generational status for Hispanic children’s diet quality (Van Hook et al 2015). However, some studies find that parents’ acculturation is unevenly related to eating specific kinds of healthy and unhealthy foods (e.g., it reduces fruit consumption, increases fast food consumption, but has no association with vegetable consumption) (Kaiser et al 2015; Erinosho et al 2012), while yet other research finds that children of more acculturated parents actually consume more fruits and vegetables than children of less acculturated parents (Chaparro et al 2015). …”
Section: Introductionmentioning
confidence: 99%